Challenges and opportunities in rapid disaster research: lessons from the field in New Mexico and Vanuatu - Scott, Mary Alice; Olszowy, Kathryn M.; Dancause, Kelsey N.; Roome, Amanda; Chan, Chim; Taylor, Hailey K.; Marañon-Laguna, Andrea; Montoya, Emilee; Garcia, Alysa; Mares, Claudia; Tosiro, Beverlyn; Tarivonda, Len (Frontiers in Sociology, 2023)
Disasters necessitate the development of rapid research to assess constantly changing on-the-ground situations, particularly for communities made “hard to reach” through historical and contemporary practices of marginalization. In this chapter, we describe two rapid research projects developed to assess needs for communities hard hit by disasters. The first is a project on the COVID-19 pandemic in southern New Mexico (USA) that was developed to provide information to local agencies that are developing programs to rebuild and revitalize marginalized communities. The second is a project on population displacement due to a volcanic eruption in Vanuatu, a low-middle income country in the South Pacific, with mental and physical health outcomes data shared with the Vanuatu Ministry of Health. We describe the similar and unique challenges that arose doing rapid research in these two different contexts, the potential broader impacts of the research, and a synthesis of lessons learned. We discuss the challenges of rapidly changing rules and regulations, lack of baseline data, lack of survey instruments validated for specific populations and in local languages, limited availability of community partners, finding funding for rapid deployment of projects, rapidly training and working with local assistants, health and safety concerns of researchers and participants, and communicating with international partners. We also specifically discuss how we addressed our own personal challenges while also conducting time-intensive rapid research. In both studies, researchers shared results with governmental and non-governmental partners who are able to use the data to design their own relief programs. While different in context, type of disaster, and research strategy, our discussion of these projects provides insights into common lessons learned for working in communities at elevated risk for the worst outcomes during disasters, such as the need for flexibility, compromise, and good working relationships with community partners.